STUDY OF PONTIANAK PORT FACILITIES AS A MAIN PORT IN WEST KALIMANTAN AREA - Kalangi, Theo Johannes Frans; Bagaskoro (Journal of Research in Business, Economics, and Education, 2020)
Increasing economic growth in West Kalimantan has made the need for smooth loading and unloading at ports increase. At present, the port in the middle of Pontianak City also handles the loading and unloading of various commodities such as crude palm oil (CPO), rubber, processed alumina mining materials, and various other basic needs of the community. For this reason, efforts are needed to improve port services in order to support West Kalimantan's economic growth. Pontianak Port has shortcomings in that the depth of the Pontianak port is the range of - 3.7 to - 5.3 m LWS, while the requirement is a minimum port pool depth of - 9 m LWS. Have a dock with a minimum capacity of 10,000 DWT. The existing quay has a length sufficient to serve ships weighing 10,000 DWT, but the depth of the port berth pool is -3.7 m LWS - 5.3 m LWS, making ships of this size limited to be able to enter during high tide. The port land area is at least 50 hectares, while the area of ??the Port of Pontianak is 202,422 m2 or around 20 hectares, and it is difficult to develop further. By looking at the results of the calculation of equipment performance, the Quayside Container Crane (QCC), Gantry Crane and Reach Stacker equipment have performance above 80%, so that it has experienced saturation, meanwhile the existing stacking area of ??47,794 m2 has not fulfilled the requirements because it has reached YOR of 86.86%. Therefore, the Port of Pontianak cannot meet the level of service fully as a Main Port, among others in terms of the availability of port facilities and infrastructure and port land development